Respuesta :

Answer:

Option B

Step-by-step explanation:

To solve the problem you must develop the sum shown.

Note that the sum goes from i = 1 to i = 3.

Therefore they ask you to make the following sum

[tex]4(0.5) ^ {1-1} + 4(0.5) ^ {2-1} + 4(0.5) ^ {3-1}[/tex]

Simplifying, we have:

[tex]4(0.5) 0 + 4(0.5) 1 + 4(0.5)^ 2\\\\4(1) + 4(0.5) + 4(0.25)\\\\4 + 2 + 1 = 7[/tex].

The answer is option B

Answer:

Option B. 7 is the correct answer.

Step-by-step explanation:

The given expression is [tex]\sum_{t=1}^{3}[{4\times (\frac{1}{2})^{t-1}}][/tex]

Now by putting the the values of t = 1, 2, 3 we get the sequence.

Then we can add the terms of the sequence

First term = [tex]4.(\frac{1}{2})^{1-1} = 4.1 = 4[/tex]

Second term = [tex]4.(\frac{1}{2})^{2-1}=4.(\frac{1}{2}) = 2[/tex]

Third term = [tex]4.(\frac{1}{2})^{3-1}=4.(\frac{1}{2})^{2}=4.\frac{1}{4}=1[/tex]

So the total of these terms will be = 4 + 2 + 1 = 7

Answer is 7.

ACCESS MORE